Assessment of self‐restraint using a functional analysis of self‐injury. Issue 4 (29th July 2015) - Scheithauer, Mindy; O'Connor, Julia; Toby, Lauryn M.
Abstract : When self‐restraint and self‐injurious behavior (SIB) co‐occur, self‐restraint might be maintained by negative reinforcement through the removal of SIB. The current study evaluated this possibility with an individual who exhibited hand‐to‐head SIB. Three functional analyses of SIB were conducted: (a) no consequences for self‐restraint, (b) self‐restraint blocked, and (c) hypothesized aversive effects of SIB blocked. The outcomes of the 3 analyses suggested that self‐restraint was maintained by negative reinforcement.